A repetição do abuso sexual intrafamiliar infanto-juvenil entre gerações - Lima, Joana Azevedo (2012)
The objective of this thesis is to analyze the feminine interfamilial sexual abuse repetition between generations. To understand this accessed reality it used the Historical-Cultural Theory from Vygotsky as theoretical outline. The theoretical categories focused on this thesis are gender, violence, family, childhood, adolescence, youth, subjectivity, consciousness and repetition. The methodological tool used to access the focused reality from the mothers looking on their daughters victims of interfamilial sexual abuse was the Speech Analysis proposed by Bakhtin. Was used an interview screenplay which related about the interfamilial sexual abuse of their daughters and then about the knowledge of other victimization histories, searching for knowing the women who also had victimization history through sexual abuse on their childhood or adolescence, as well as the subjectivities which emerge from these experiences. Following, it was constituted an interview corpus and then, the analysis proceeded. The Bakthin Speech Analysis elements analyzed on the participants speeches were dialogism, discursive genders, polyphony and statements. The participants speeches were categorized as a) Victimized mother: the participants speech about the interfamilial child-youth sexual abuse suffered by her daughter; b) Victimized woman: the speech about interfamilial child-youth sexual abuse the participants suffered; c) The repetition sense of feminine interfamilial child-youth sexual abuse between generations from mothers voice. Through participants speech can be perceived constituted subjects from the interfamilial sexual abuse repetition experiences between generations, hers and the daughter s. They are women, mothers and victims who as confronted with their daughters sexual abuse reality; they suffer as women, who feel themselves doubly victimized for the fact of realizing the repetition between generations in their family of the male dominance and the interfamilial sexual abuse. Furthermore, the fact of having the knowledge of the interfamilial sexual abuse of their daughters served as a reflection for the memory of their own interfamilial sexual abuse suffered on their childhood, making them relive the experience from the past and to emerge the child-youth interfamilial sexual abuse repetition between generations reflected in the fact that the mother and daughter had been abused on their childhood, having the same level of affinity with the abuser, repeating behaviors which their mothers had at the time of their victimization in the childhood, of seeing the repeated behavior on their daughters against the victimization and decisions as not to reveal to nobody the abuse.